ВЛИЯНИЕ ОБРАЗОВАТЕЛЬНОЙ СИСТЕМЫ ОРГАНИЗАЦИИ АНГЛИЙСКОГО ЯЗЫКА НА УЧАЩИХСЯ НАЧАЛЬНЫХ КЛАССОВ НА ОСНОВЕ СОВРЕМЕННЫХ ТЕХНОЛОГИЙ - Комолова Икбол Адхамовна (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
Information technologies have affected every aspect of human activity and have a potential role to play in the field of education and training, specially, in distance education to transform it into an innovative form of experience. The need of new technologies in teaching learning process grows stronger and faster. The information age becomes an era of knowledge providing sound and unmatched feasibility for discovery, exchange of information, communication and exploration to strengthen the teaching learning process. Information technologies help in promoting opportunities of knowledge sharing throughout the world. These can help the teachers and students having up-to-date information and knowledge